2003
DOI: 10.1002/cne.10823
|View full text |Cite
|
Sign up to set email alerts
|

Comparative distribution of neuropeptide Y Y1 and Y5 receptors in the rat brain by using immunohistochemistry

Abstract: Neuropeptide Y (NPY) Y1 and Y5 receptor subtypes mediate many of NPY's diverse actions in the central nervous system. The present studies use polyclonal antibodies directed against the Y1 and Y5 receptors to map and compare the relative distribution of these NPY receptor subtypes within the rat brain. Antibody specificity was assessed by using Western analysis, preadsorption of the antibody with peptide, and preimmune serum controls. Immunostaining for the Y1 and Y5 receptor subtypes was present throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
198
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(221 citation statements)
references
References 105 publications
(126 reference statements)
19
198
1
3
Order By: Relevance
“…The MePD is an interesting forebrain area where to look for the central control of feeding behavior due to its relevant neural connections and the presence of neurotransmitters or neuropeptides that modulate this activity, such as neuropeptide Y (Wolak et al, 2003), cholecystokinin (De Vries and Simerly, 2002), and urocortin 3 (Cavalcante et al, 2006). Comparatively, it was reported that glutamate microinjected in the lateral hypothalamus induced a dose-dependent eating response in satiated male rats of up to 5 g of food within 1 hr (Stanley et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The MePD is an interesting forebrain area where to look for the central control of feeding behavior due to its relevant neural connections and the presence of neurotransmitters or neuropeptides that modulate this activity, such as neuropeptide Y (Wolak et al, 2003), cholecystokinin (De Vries and Simerly, 2002), and urocortin 3 (Cavalcante et al, 2006). Comparatively, it was reported that glutamate microinjected in the lateral hypothalamus induced a dose-dependent eating response in satiated male rats of up to 5 g of food within 1 hr (Stanley et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TRH-expressing neurons in the PVN of the mouse are known to express Y1 receptor-like immunoreactivity (Broberger et al, 1999). Unlike the MC3 receptor, MC4 receptor mRNA (Mountjoy et al, 1994) as well as Y1 and Y5 receptor immunoreactivity (Wolak et al, 2003) are found in both parvicellular and magnocellular neurons of the PVN as recently reviewed , suggesting direct effects of NPY and melanocortins on the thyrotropic axis at the level of the hypothalamus. Indeed, central administration of NPY, Y1 or Y5 receptor agonists, AgRP or MC4 receptor antagonists to normal rodents significantly reduces function of the thyrotropic axis, indicated by reductions in expression of TRH in the PVN, and a decrease in circulating concentrations of TSH and T3 or T4 (Fekete et al, 2001, Fekete et al, 2002a, Fekete et al, 2002b, Small et al, 2001and Kim et al, 2000.…”
Section: Preston Et Almentioning
confidence: 96%
“…Neuropeptide Y (NPY) is a 36-amino acid neuroactive peptide found in the cerebral cortex, hippocampus, hypothalamus, thalamus, amygdala, striatum, brainstem, and cerebellum (Allen et al, 1983;Dumont et al, 1993;Parker and Herzog, 1999;Wolak et al, 2003). NPY colocalizes with somatostatin, gamma-aminobutric acid (GABA), and nitric oxide synthase (Bidmon et al, 2001a;Kowianski et al, 2004;Kubota et al, 1994), and can modulate neuronal excitability by multiple pre-and postsynaptic mechanisms under both physiological and pathophysiological conditions.…”
Section: Introductionmentioning
confidence: 99%